2014
DOI: 10.1109/jsen.2014.2299063
|View full text |Cite
|
Sign up to set email alerts
|

An Instrumented Insole for Long Term Monitoring Movement, Comfort, and Ergonomics

Abstract: We present a new electronic insole for wireless monitoring of motor activities and shoe comfort. The proposed device, equipped with both ZigBee transmission and local data storage allows unobtrusive, long term monitoring of subjects outside the laboratory, during natural behavior activites, such as daily living and sports. The system detailed in this work includes humidity and temperature sensors, as well as a three axis accelerometer and four pressure sensors, all fitted within a 3.7 mm thick insole. Prelimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Although Bluetooth and Zigbee do not meet the requirements in terms of data-rate, reliability, and SAR of certain medical applications (e.g., in hospital environments) [20], most of the reported WBAN implementations rely on these standards [25]- [30]. However, to the best of the authors' knowledge, no realization of WBANs has been reported based on IEEE 802.15.6, which can be explained by the availability of Bluetooth and Zigbee transceivers and their ease of use compared to the former.…”
Section: Existing Wireless Technologies For Wbans and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Bluetooth and Zigbee do not meet the requirements in terms of data-rate, reliability, and SAR of certain medical applications (e.g., in hospital environments) [20], most of the reported WBAN implementations rely on these standards [25]- [30]. However, to the best of the authors' knowledge, no realization of WBANs has been reported based on IEEE 802.15.6, which can be explained by the availability of Bluetooth and Zigbee transceivers and their ease of use compared to the former.…”
Section: Existing Wireless Technologies For Wbans and Related Workmentioning
confidence: 99%
“…Concerning Zigbee applications, a wearable system was designed in [30] comprising of an accelerometer and temperature and humidity sensors, using an IEEE 802.15.4 compatible transceiver capable of implementing Zigbee protocols and transmitting at 2 mW. Also, a wearable system equipped with GPS and 3-lead ECG was proposed in [32] for the purpose of fall detection and assisting elderly people.…”
Section: Existing Wireless Technologies For Wbans and Related Workmentioning
confidence: 99%
“…Other studies have been directed toward the development of new instrumented insoles for clinical tests with low-cost and often with wireless communications such as presented in [28], [29]. Those insoles were used for ergonomic evaluation in standing posture and for lower limb prosthetic.…”
Section: A Technologies For Gait and Balance Disorder Analysismentioning
confidence: 99%
“…A tri-axial accelerometer integrated with humidity, temperature and four pressure sensors was embedded in a less than 4 mm-thick electronic insole for wireless monitoring of motor activities and shoe comfort. Preliminary experiments demonstrated that the device is reliable and may be worn without causing discomfort even for long periods of time, thus suggesting that it may represent a useful device in applications ranging from ergonomics studies on footwear, rehabilitation and also sports [ 67 ].…”
Section: Mems-based Sensor Technologies For Human Centred Applicatmentioning
confidence: 99%